Matrix Coding of Hypertension Prevention Behavior of Students in Semarang City - Suryana, Erni; Kuswardinah, Asih; Wijayanti, Yuni (Public Health Perspective Journal, 2021)
Hypertension or high blood pressure is a serious medical condition that significantly increases the risk of heart attack, kidney failure, and blindness. Hypertension is one of the causes of premature death in the worldwide. 34.1% of Indonesian adults aged 18 years and over are affected by hypertension. The purpose of this study is to describe the results of matrix coding of hypertension prevention behavior of students in Semarang city. This research is a descriptive qualitative research. The data were obtained by in-depth interviews with 25 sources using purposive sampling technique. The data analysis used qualitative analysis using the NVivo 12 Plus application that was  presented in the form of matrix coding which was then described. The results showed that hypertension prevention behavior carried out by students in Semarang City by doing: 1) limiting high-fat foods, 2) reducing excess salt consumption, 3) reducing trans fats, 4) consuming balanced vegetables and fruits, 5) avoiding cigarettes, and 6) do sports and physical activity. Morover, there are still things that are not known by students in preventing hypertension, such as consuming alcohol which can actually increase the risk of hypertension.